1985
DOI: 10.1017/s0021859600044191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea and neem cake coated urea on yield, and concentration and quality of essential oil in Java citronella (Cymbopogon winterianus Jowitt)

Abstract: Java citronella (Cymbopogon winterianus Jowitt) is an important perennial aromatic grass cultivated in different parts of India. The steam-volatile essential oil from the citronella herb is widely used in perfumery, in manufacture of deodorants and mosquito repellent creams and in flavouring beverages. Systematic cultivation of this crop is being taken up and application of large quantities of N fertilizers was found to increase yield (Narayana et al. 1975; Bommegowda, 1978; Singh, Pathak & Bodoloi, 1980; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…In palmarosa, application of up to 240 kg N/ha/yr in red soils of Bangalore (Prakasa Rao et al, 1985a), 40 kg N/ha in Delhi (Pareek et al, 1983a), 25.50 kg N/ha in Indore (Maheswari et al, 1992), 25 kg N/ha in Kerala , 80 kg N/ha in Tamil Nadu (Barooah and Khader, 1990) was recommended. Low recoveries of N especially by citronella have been studied in detail (Prakasa Rao et al, 1983b) and improved methods of N application such as split application (Prakasa Rao 1988d), use of NCU (Prakasa Rao et al, 1985b), USG (Prakasa Rao et al, 1984b), amelioration of Fe deficiency (Puttanna et al, 1993), use of organics (Puttanna and Prakasa Rao, 1997) were found to improve the NUE in citronella (table 3). Being perennial, gradual depletion of P and K in long run and need for application of these nutrients in palmarosa has been emphasized (Prakasa Rao et al, 2001).…”
mentioning
confidence: 99%
“…In palmarosa, application of up to 240 kg N/ha/yr in red soils of Bangalore (Prakasa Rao et al, 1985a), 40 kg N/ha in Delhi (Pareek et al, 1983a), 25.50 kg N/ha in Indore (Maheswari et al, 1992), 25 kg N/ha in Kerala , 80 kg N/ha in Tamil Nadu (Barooah and Khader, 1990) was recommended. Low recoveries of N especially by citronella have been studied in detail (Prakasa Rao et al, 1983b) and improved methods of N application such as split application (Prakasa Rao 1988d), use of NCU (Prakasa Rao et al, 1985b), USG (Prakasa Rao et al, 1984b), amelioration of Fe deficiency (Puttanna et al, 1993), use of organics (Puttanna and Prakasa Rao, 1997) were found to improve the NUE in citronella (table 3). Being perennial, gradual depletion of P and K in long run and need for application of these nutrients in palmarosa has been emphasized (Prakasa Rao et al, 2001).…”
mentioning
confidence: 99%